The Impact of Financial Development on Income Inequality: Evidence from OECD Countries - Çiğdem Karış; Dilek Çil (Istanbul Business Research)
The financial system has an important component which adds to social welfare. Investment and consumption expenditures contribute to the increase in production by meeting the capital requirement. The study examines the impact of financial development on income inequality for 13 member nations of the OECD between 1993 and 2017 in light of the panel data method. In the study, income inequality is used as a proxy for the GINI coefficient, while the banks’ domestic credit to the private sector is utilized to represent financial development. In addition, the model utilizes control variables, including per capita income, trade openness, inflation, and public spending. The panel data regression results reveal that financial development has a positive effect on income inequality. The results of the paper support the Income Inequality Widening Hypothesis, which suggests that the situation which favours individuals with high income levels who have access to financial resources continues when financial development increases, which in turn increases income inequality.